1981
DOI: 10.2307/2061051
|View full text |Cite
|
Sign up to set email alerts
|

Return and Other Sequences of Migration in the United States

Abstract: We examine repeat migration sequences in the United States especially those that entail a return, using data from the Panel Study of Income Dynamics. Our guiding hypotheses derive from the concepts of location-specific capital and imperfect information. Descriptive analysis elucidates the dynamics, tempo, and differential frequency of repeat migration among various socioeconomic groups. Results disclose difference among migrants who choose to return or move onward to a new location, or do not move again, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(135 citation statements)
references
References 15 publications
7
123
1
4
Order By: Relevance
“…"Location-specifi c capital," a generic term for factors that tie someone to a particular place (DaVanzo and Morrison 1981;Paxson and Rouse 2008), includes concrete assets and other features specifi c to a place that are more valuable to an individual in one location than in another, such as job seniority, an established clientele, a license to practice a particular profession in a certain area, personal knowledge of an area, community ties, and social networks. Although location-specifi c capital usually does not depreciate over time, Hurricane Katrina potentially destroyed a great deal of location-specifi c capital (Paxson and Rouse 2008).…”
Section: Location-specifi C Capitalmentioning
confidence: 99%
“…"Location-specifi c capital," a generic term for factors that tie someone to a particular place (DaVanzo and Morrison 1981;Paxson and Rouse 2008), includes concrete assets and other features specifi c to a place that are more valuable to an individual in one location than in another, such as job seniority, an established clientele, a license to practice a particular profession in a certain area, personal knowledge of an area, community ties, and social networks. Although location-specifi c capital usually does not depreciate over time, Hurricane Katrina potentially destroyed a great deal of location-specifi c capital (Paxson and Rouse 2008).…”
Section: Location-specifi C Capitalmentioning
confidence: 99%
“…This strand of literature stresses the notion of regional migration as an investment in human capital with associated costs that render returns (Sjastaad, 1962;Greenwood, 1997). Borjas et al (1992, 170) rely on the concept of location-specific capital (see also DaVanzo / Morrison, 1981). This approach suggests that returns to regional migration become only effective after some time because regional migrants have to acquire knowledge about regional labor markets in the destination area first.…”
Section: Causal Effects: Immediate Migration Returns and Wage Growth mentioning
confidence: 99%
“…Several studies have found that people tend to return to places where they lived before (DaVanzo, 1981;DaVanzo and Morrison, 1981;Fischer and Malmberg, 2001;Morrison and DaVanzo, 1986;Newbold, 1997Newbold, , 2001; for the Netherlands: Harts and Hingstman, 1986;Nicolaas and Sprangers, 2000). Return moves are made for several reasons: because of ties to the place of origin (that is, the social space and activity space); as a corrective move (out of regret about having moved away; see Morrison and DaVanzo, 1986;Newbold, 1996); or emotional attachment to a place (Rubinstein and Parmelee, 1992;Feldman, 1996).…”
Section: Residential Experiencementioning
confidence: 99%